(untitled) (Acta Judicial Journal, 2018)
The 2008 legal reform on the exclusion from the Regulation concerning the compulsory motor insurance demands concretization about the concept of “acts classifiable as use of a vehicle”, as well as the places excluded by the insurance. This qualitative element determines the applicability of the Regulation and produces anomalous effects that generates the contradiction of requiring a voluntary insurance to travel through specific areas at ports and airports.